2017
DOI: 10.1103/physrevapplied.8.014017
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Thermodynamic Bound for the Efficiency of Light-Emitting Diodes

Abstract: A thermodynamic model for light-emitting diodes (LEDs) is developed by considering energy and entropy flows in the system. Thermodynamic constraints have previously been considered separately for the reversible process of electroluminescence in LEDs and for light extraction and collimation in other optical systems. By considering both processes in the LED model, an irreversible upper bound for the conversion of electrical energy to optical energy is derived and shown to be higher than unity, but tighter and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Fundamentally, EL cooling is based on simple thermodynamics of light 5 emitting diodes (LEDs), allowing a diode to emit a photon with an energy larger than the bandgap of the semiconductor material the LED is made of. This applies even when the bias voltage of the LED is arbitrarily small [3][4][5].…”
mentioning
confidence: 99%
“…Fundamentally, EL cooling is based on simple thermodynamics of light 5 emitting diodes (LEDs), allowing a diode to emit a photon with an energy larger than the bandgap of the semiconductor material the LED is made of. This applies even when the bias voltage of the LED is arbitrarily small [3][4][5].…”
mentioning
confidence: 99%
“…165 Further, a theoretical study showed that for the visible and infrared ultra-low-power LEDs the WPE can reach up to 130% and even 250%. 166 On the other hand, LiFi offers higher speed in comparison to radio wave communication protocols because of wider bandwidth. § § 164,167,168 These two facts (high WPE of LEDs and high speed of LiFi), alongside with continuously increasing flow of information flow, ¶ ¶ 169 make shortly LED-based LiFi technology a promising solution for wireless communication.…”
Section: Research Area 5 Integration and Control Of Light-generatingmentioning
confidence: 99%
“…Then, the cooled electrodes will cool the ambient next during the solar cell operation. Semiconductor devices with similar structure, which cool down the ambient for the operation, can exist in reality as found in light-emitting diodes (LEDs) (namely, refrigerating LEDs [48][49][50][51][52] ). However solar cells are the devices aimed for long-term stand-alone operation requiring the stability at a long-time scale.…”
Section: B Another Limiting Case: Heat-isolated Phonon Reservoirsmentioning
confidence: 99%